Komposisi Jenis, Serapan Karbon Dioksida dan Produksi Oksigen Vegetasi Berkayu di Hutan Kemasyarakatan Batu Bulan Kabupaten Gunung Mas Kalimantan Tengah: Species Composition, Carbon Dioxide Uptake and Oxygen Production of Woody Vegetation in The Batu Bulan Community Forest Gunung Mas District, Central Kalimantan - Junaedi, Ajun; Aruan, Jenifer; Yosep, Yosep; Penyang, Penyang; Surasana, I Nyoman; Rizal, Moh (HUTAN TROPIKA, 2024)
Community Forestry is one of the schemes in provides access to forest management legally to the community, so community forestry has a role in supporting the sustainability of forest functions. In line with the principles of sustainable forest management, community forestry management is required to maintain a balance of ecological, economic, and social aspects. The purpose of the study was to identify the species composition and estimate the potential biomass reserves, carbon, carbon dioxide (CO2) absorption, and oxygen (O2) production of woody vegetation in the Batu Bulan Community Forest, Tusang Raya Village, West Rungan District, Gunung Mas Regency, Central Kalimantan Province. Vegetation data collection with vegetation analysis techniques using the plot line method. Data from the analysis of woody vegetation was then calculated for the number of species, Shannon Wienner species diversity index (H'), vegetation density, and Important Value Index (IVI). Calculation of vegetation biomass using destructive and non-destructive methods. While the calculation of carbon, CO2 uptake, and O2 production of woody vegetation were each calculated using SNI 7724 (2019), IPCC (2006), and Nowak et. al (2007). The results showed that the number of woody vegetation species found was 31 species included in 19 families with a Shannon Wienner species diversity index value of 2.81 ("medium" category). Tree and pole-level woody vegetation was dominated by Laban (Vitex pubescens Vahl.), while sapling and seedling levels were dominated by Rubber (Hevea brasiliensis) and Palasit (Canarium sp), respectively. The potential reserves of biomass, carbon, CO2 uptake, and O2 production of woody vegetation were 70.12 tons/ha, 32.81 tonsC/ha, 120.96 tonsCO2/ha, and 88.01 tonsO2/ha, respectively.